2013
DOI: 10.1007/s00248-013-0188-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Vibrio with Virulence Genes Detected in Pacific Harbor Seals (Phoca vitulina richardii) Off California: Implications for Marine Mammal Health

Abstract: Hughes, Stephanie Nichole, "Dynamics of Vibrio with virulence genes detected in Pacific harbor seals (Phoca vitulina richardii) off California: implications for marine mammal health" (2012

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 73 publications
(119 reference statements)
0
9
0
Order By: Relevance
“…Additional microbes of concern in SRKW exhaled breath samples included pathogenic Vibrio alginolyticus 22 and opportunistic pathogenic species of Aspergillus spp. 23 , which are associated with mortality in Rachycentron canadum 22 and pulmonary disease in bottle nose dolphins 23 , respectively, and have previously been recovered from other stranded and live captured marine mammal species 2426 .…”
Section: Discussionmentioning
confidence: 99%
“…Additional microbes of concern in SRKW exhaled breath samples included pathogenic Vibrio alginolyticus 22 and opportunistic pathogenic species of Aspergillus spp. 23 , which are associated with mortality in Rachycentron canadum 22 and pulmonary disease in bottle nose dolphins 23 , respectively, and have previously been recovered from other stranded and live captured marine mammal species 2426 .…”
Section: Discussionmentioning
confidence: 99%
“…Both the persistence and abundance of vibrios are related to several parameters, whose influence can differ according to the geographic region . Moreover, the available dissolved organic matter and the plankton, temperature and salinity seem to be related to the abundance, distribution, and persistence of Vibrio populations in aquatic environments (Eiler et al 2006;Hughes et al 2013), although the different species vary in both minimal Na + concentrations and temperature requirements (Farmer et al 2005;Urakawa and Rivera 2006). The ability to enter a viable but not culturable state (Rollins and Colwell 1986) prolongs their survival in the environment, especially during winter (Maugeri et al 2004).…”
Section: Introductionmentioning
confidence: 97%
“…Despite the growing importance of microorganisms as agents of infectious diseases in aquatic mammals, as well as their use as indicators of the health of aquatic ecosystems (Bossart 2010), studies on the virulence features of bacteria and fungi from these animals are still scarce. Hughes et al (2013), for example, reported the presence of virulence genes in Vibrio strains from harbor seals in California, while Cordeiro et al (2014) have assessed the production of virulence factors by C. tropicalis from veterinary sources, including cetaceans stranded in Brazil.…”
Section: Introductionmentioning
confidence: 99%